Doing quantitative research in the social sciences an integrated approach to research design, measurement and statistics - Black, Thomas R. (SAGE, 1999)
This original textbook provides a comprehensive and integrated approach to using quantitative methods in the social sciences. Thomas R Black guides the student and researcher through the minefield of potential problems that may be confronted, and it is this emphasis on the practical that distinguishes his book from others which focus exclusively on either research design and measurement or statistical methods. Focusing on the design and execution of research, key topics such as planning, sampling, the design of measuring instruments, choice of statistical text and interpretation of results are examined within the context of the research process. In a lively and accessible style, the student is introduced to research design issues alongside statistical procedures and encouraged to develop analytical and decision-making skills.